SEASONAL CYCLE OF TESTICULAR MATURATION AND INTERSTITIAL CELL ACTIVITY IN THE HILL-STREAM TELEOST, PUNTIUS DUKAI (DAY) - Joshi, K D; Joshi, P C (Indian Journal of Fisheries, 2011)
The testes of Punt ius dukai consist of seminiferous lobules and stroma. The anterior three-fourth part of thetestis is fertile whereas the hindmost region is histologically sterile. The testes show discontinuousspermatogenic cycle, and pass through the successive stages of growth, maturation, activation, depletionand rest during annual cycle. The stroma contains interestitial cells which undergo histological and histochemicalchanges in association with the spermatogenic cycle. These cells show sign of hyperactivitywhen meiosis and spermiogenesis occur in the testicular lobules.